2020
DOI: 10.1007/s11606-020-06264-5
|View full text |Cite
|
Sign up to set email alerts
|

Asian-Americans and Pacific Islanders in COVID-19: Emerging Disparities Amid Discrimination

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic. In the USA, the burden of mortality and morbidity has fallen on minority populations. The understanding of the impact of this pandemic has been limited in Asian-Americans and Pacific Islanders (AAPIs), though disaggregated data suggest disproportionately high mortality rates. AAPIs are at high risk for COVID-19 transmission, in part due to their over-representation in the essential workforce, but also due to cultural factors, such as intergenerational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 30 publications
0
124
0
2
Order By: Relevance
“…NHOPI veterans in our sample had higher risk of COVID-19 infection over the summer. Many Pacific Islander individuals work in healthcare [ 29 ], which may increase their risk of COVID-19 infection. We also found higher mortality over the summer in Asian veterans, whereas some studies, conducted with data from the early months of the pandemic, suggested that Asian individuals in the general U.S. population had similar or lower COVID-19-related mortality than non-Hispanic White individuals [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…NHOPI veterans in our sample had higher risk of COVID-19 infection over the summer. Many Pacific Islander individuals work in healthcare [ 29 ], which may increase their risk of COVID-19 infection. We also found higher mortality over the summer in Asian veterans, whereas some studies, conducted with data from the early months of the pandemic, suggested that Asian individuals in the general U.S. population had similar or lower COVID-19-related mortality than non-Hispanic White individuals [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic caused by novel coronavirus SARS-CoV-2, fear, rumors, and misconceptions about the novel coronavirus have placed Asian Americans in the spotlight of blame and harassment [1][2][3][4][5]. Instead of preventing discrimination and xenophobia, government officials repeatedly labeled the virus the "Wuhan coronavirus" or the "China virus," potentially accelerating COVID-19 related racial attacks on Asian Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Predicators of COVID-19 pandemic-related stress among Bhutanese and Burmese refugee participants in the USA in 2020, applying bivariate analysis and adjusted ordinal logistic regression models a We applied the model command to measure the proportional odds assumption of ordinal logistic regression models. The p value of this test is equal to 0.604, indicating the model does not violate the proportional odds assumption b This is an ordinal variable describing the number of different types of stress reported by each survey participant (0, 1, 2,3,4) …”
mentioning
confidence: 99%
“… Policies and regulations should be enforced to ensure that emergency services are always provided to patients within a healthcare facility Avoidance of victims [5,[7][8][9][10][11][12][13][14][15][16][17][18][19]  In Italy, reports suggest that the public avoided people perceived to be of Chinese origin  In Burkina Faso, neighbors started avoiding a patient who was tested for COVID-19  In India, airplane crew members were stigmatized  In Egypt, a driver refused to transport a man of Chinese origin  In the USA, Black and Asian adults report more adverse events since the start of the pandemic; individuals who wear face masks feel discriminated  In Nepal, febrile patients were avoided by some healthcare institutions  In France, minority ethnic areas had to undergo longer curfews than other neighborhoods; Asians were kicked off from public transport  In the Philippines, a priest and a worker were socially excluded due to a potential contact with a COVID-19 patient and due to flu-like symptoms  In Bangladesh, a man was ostracized after developing fever and cough; he eventually committed suicide  In China, foreigners have been barred from entering some restaurants and some fitness facilities  Africans have been evicted from their apartments…”
Section: Mini Review Articlementioning
confidence: 99%